2019
DOI: 10.1538/expanim.18-0084
|View full text |Cite
|
Sign up to set email alerts
|

Bone microstructure and metabolism changes under the combined intervention of ketogenic diet with intermittent fasting: an <i>in vivo</i> study of rats

Abstract: Ketogenic diet (KD) has been used in epilepsy for decades, but previous studies found it may cause severe bone loss. Every-other-day ketogenic diet (EODKD), the combination of KD with intermittent fasting, showed better potential for seizure control recently, while its effects on bone remain unknown. This study aims to establish different ketogenic rat models and compare the influence of EODKD with KD on bone microstructure and metabolism. Thirty male Sprague-Dawley rats were divided into Control, KD and EODKD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…However, it was firstly reported by Hahn that KD had deleterious effects on bone mass in children who maintained this regimen in long term (13). Our previous studies also confirmed that KD compromised bone micro-structures and reduced bone biomechanics in rodents (14)(15)(16)(17)(18). However, the different effects of streptozotocin-induced hyperglycemia and KD-induced hyperketonemia on bone microstructures and biomechanics have not been elucidated.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, it was firstly reported by Hahn that KD had deleterious effects on bone mass in children who maintained this regimen in long term (13). Our previous studies also confirmed that KD compromised bone micro-structures and reduced bone biomechanics in rodents (14)(15)(16)(17)(18). However, the different effects of streptozotocin-induced hyperglycemia and KD-induced hyperketonemia on bone microstructures and biomechanics have not been elucidated.…”
Section: Introductionsupporting
confidence: 64%
“…Researches on the effects of hyperketonemia induced by KD on bone microstructures and bone qualities in rodents were performed in our previous studies. KD deteriorated microstructures of cancellous bone by decreasing bone mass and impairing biomechanical properties, as well as inhibiting osteogenic process and enhancing osteoclastic process in the BMSCs (15,17). Akihiro et al (33) found that ketone bodies bidirectionally modulate osteoblast functions, which suggests that ketone bodies is an important endogenous factor that regulates bone metabolism in both physiological and pathological situations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effect of KD on liver steatosis [125,126], glucose homeostasis [126,127], and dyslipidemia [53,128] remain controversial. Recent evidence expresses potential concerns with the LC/KD compromising bone health in rodents as several studies reported decreases in bone mineral content and bone density [129,130,131]. In a transgenic mouse model of neurodegeneration, KD caused acceleration of the neurodegenerative process and induced mitochondrial dysfunction, despite the promotion of mitochondrial biogenesis [132].…”
Section: Potential Side Effects Of Ketogenic Dietsmentioning
confidence: 99%
“…Serum ketone testing may also provide us with a regulatory measure to confirm dietary adherence. Not all tissues, however, may benefit from these dietary regimens, particularly bone tissue with concern for resorption and increased catabolism under a ketogenic diet [ 84 , 85 ]. Nevertheless, the behavioral basis of these interventions, along with its unfamiliarity amongst patients and providers, may require the expertise and services of nutritionists to implement these dietary regimens safely and adequately.…”
Section: Discussionmentioning
confidence: 99%